Mental workload and road environment complexity: subjective assessments - Nurainaa Kabilmiharbi; Nor Kamaliana Khamis (Penerbit Universiti Kebangsaan Malaysia, 2024)
Since 2011, mental workload has been one of the top 10 causes of accidents in Malaysia, accounting for over a thousand fatalities yearly. Mental workload is defined as a comparable mediating variable to attention. The aim of this study is to identify the fundamental causes and influences that affect the difficulty of the road environment and vehicle task, as well as their impact on the driver’s health. In this study, subjective measurement is used to assess the level of mental workload of drivers which includes NASA-TLX and KSS on two different road environment condition namely urban and rural road environment. The findings show that the complexity of the road environment has a significant effect towards the mental workload of a driver. The average NASA-TLX score for urban roads is higher than the average score for rural roads while, the results for KSS level indicates higher drowsiness level among the drivers when driving on a rural road as opposed to an urban road. These results may serve as a guide for future research into the mental workloads of drivers in various types of complex road environments, as well as a practical guide for car manufacturers, agencies responsible for road safety, and researchers to improve the safety design of cars and consider external factors related to road environment complexity when designing roads.